2012
DOI: 10.3340/jkns.2012.51.1.20
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study on the Change in Lumbar Lordosis When Standing, Sitting on a Chair, and Sitting on the Floor in Normal Individuals

Abstract: ObjectiveTo compare radiographic analysis on the sagittal lumbar curve when standing, sitting on a chair, and sitting on the floor.MethodsThirty asymptomatic volunteers without a history of spinal pathology were recruited. The study population comprised 11 women and 19 men with a mean age of 29.8 years. An independent observer assessed whole lumbar lordosis (WL) and segmental lordosis (SL) between L1 and S1 using the Cobb's angle on lateral radiographs of the lumbar spine obtained from normal individuals when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 16 publications
(19 reference statements)
1
18
0
1
Order By: Relevance
“…was similar in this cohort to previously published figures [27,28]. Our results show a trend for the seated extension posture to have a less lordotic curvature than in upright stranding (albeit not significantly) which is similar to previous studies that have reported the lumbar lordosis to be greater in standing than sitting [29][30][31][32]. Small differences in M1 scores at larger angles of flexion indicate that some individuals may have already reached their comfortable end range of motion for the spine in the flex 60°posture [33] and, therefore, find it difficult to flex any further for the hang-flex posture.…”
Section: Discussionsupporting
confidence: 92%
“…was similar in this cohort to previously published figures [27,28]. Our results show a trend for the seated extension posture to have a less lordotic curvature than in upright stranding (albeit not significantly) which is similar to previous studies that have reported the lumbar lordosis to be greater in standing than sitting [29][30][31][32]. Small differences in M1 scores at larger angles of flexion indicate that some individuals may have already reached their comfortable end range of motion for the spine in the flex 60°posture [33] and, therefore, find it difficult to flex any further for the hang-flex posture.…”
Section: Discussionsupporting
confidence: 92%
“…To this end, the dis tances and the angles between the intervertebral joints of lumbar spine segments T12-S1 were measured. The results showed that Cobb's angle of the lumbar spine region was within a normal range in all subjects [18].…”
Section: Customized Lumbar Spine Modelmentioning
confidence: 97%
“…Another finding is that the disability scores for sitting on the floor were not different among groups who had the fusion at L4-L5 or at L5-S1. Bae et al 28 described in a radiological study of a healthy population on the change of segmental and whole lumbar lordosis according to the postures of standing, sitting in a chair, and sitting on the floor in ''oriental style'' that 66.2% of the loss of the whole lumbar lordosis during the postural change from sitting in a chair to sitting on the floor occurs at L4-L5, whereas only 6.9% at L5-S1. It was expected that back pain while sitting on the floor after lumbar fusion would be most serious when the fusion is done at the L4-L5 level.…”
Section: Discussionmentioning
confidence: 99%